Isolation of lactic acid bacteria and amylolytic lactic acid bacteria from suitable sources - Nurul Izzah Mokhtar Kamal, 1988-; Zainoha Zakaria, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010